The validity of project-based learning device on momentum and impulse materials in increasing students creativity - Farah Hulwani Lala Junti; Gunawan Gunawan; Ahmad Harjono; Ahmad Busyairi; Kosim Kosim (Jurnal Pijar Mipa, 2021)
This study aims to determine the validity of project-based learning devices to increase students' creativity on momentum and impulse materials. It is a research and development type with a 4D (Define, Design, Develop, and Disseminate) model developed by Thiagarajan. The validity of the product developed in this study was tested by 2 Physics education expert lecturers and 3 Physics teacher practitioners. This study indicates that the learning device is feasible to proceed to the operational trial phase in learning activities. Based on the assessment by the device validator, it obtained an average validity value of 86.72% with a very feasible category. The student responses to the developed device are positive, with an average value of 100%.